Pariwisata Berkelanjutan Songket Silungkang Sebagai Warisan Budaya di Kota Sawahlunto - Relyn Putri Amnelta (Journal of Tourism Sciences, Technology and Industry, 2026)
Silungkang Songket is one of the intangible cultural heritages of the Minangkabau people that has historical and aesthetic value, and has the potential to become a cultural tourism attraction in Sawahlunto City. However, the development of modernization, the declining interest of the younger generation in weaving activities, and the less than optimal management and promotion have caused the existence of Silungkang Songket to face various challenges. Therefore, it is necessary to implement the concept of sustainable tourism that pays attention to the balance between economic, socio-cultural, and environmental aspects. This study aims to analyze the implementation of sustainable tourism in the preservation of Silungkang Songket as a cultural heritage in Sawahlunto City. The type of research in this study is descriptive qualitative research with data collection methods used in the form of observation, interviews, documentation, and literature studies. The data analysis methods used in this study are data reduction, data presentation, and drawing conclusions using triangulation techniques to test the validity of the data. The results of the study indicate that the implementation of sustainable tourism in Silungkang Songket has made a positive contribution to improving the community's economy through weaving activities and selling songket products. From a socio-cultural aspect, the existence of songket is able to maintain the cultural identity of the Silungkang community through the inheritance of weaving skills and the implementation of cultural activities. Meanwhile, from an environmental perspective, the songket industry still maintains environmental considerations through the use of household production facilities and efforts to maintain environmental cleanliness. Therefore, developing Silungkang songket through sustainable tourism can be a strategy for preserving cultural heritage while improving the well-being of local communities.